A study of the prevalence of bacterial pathogens in the air of the different areas of Dhaka city - Monisha, Noshin Anjum; Rahman, Md. Hafizur (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.